2020
DOI: 10.1038/s41467-020-18729-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of Tet-mediated RNA hydroxymethylcytosine in mouse ES cells and during differentiation

Abstract: Tet-enzyme-mediated 5-hydroxymethylation of cytosines in DNA plays a crucial role in mouse embryonic stem cells (ESCs). In RNA also, 5-hydroxymethylcytosine (5hmC) has recently been evidenced, but its physiological roles are still largely unknown. Here we show the contribution and function of this mark in mouse ESCs and differentiating embryoid bodies. Transcriptome-wide mapping in ESCs reveals hundreds of messenger RNAs marked by 5hmC at sites characterized by a defined unique consensus sequence and particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 72 publications
7
65
0
Order By: Relevance
“…The PSPC1-TET2 mediated 5hmC deposition on MERVL transcripts resulted in their destabilization and subsequent degradation (Guallar et al, 2018 ). In addition, both TET1 and TET2 deposit 5hmC in mRNAs in genes that are fundamental for pluripotency, such as Jarid2 and Eed , and can result in reduced mRNA stability (Lan et al, 2020 ). As a consequence of the transcript destabilization, pluripotency genes that would be expressed too highly acquire appropriate expression levels and adequately repress the expression of lineage-specifying factors (Lan et al, 2020 ).…”
Section: Mechanisms Of Tet Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSPC1-TET2 mediated 5hmC deposition on MERVL transcripts resulted in their destabilization and subsequent degradation (Guallar et al, 2018 ). In addition, both TET1 and TET2 deposit 5hmC in mRNAs in genes that are fundamental for pluripotency, such as Jarid2 and Eed , and can result in reduced mRNA stability (Lan et al, 2020 ). As a consequence of the transcript destabilization, pluripotency genes that would be expressed too highly acquire appropriate expression levels and adequately repress the expression of lineage-specifying factors (Lan et al, 2020 ).…”
Section: Mechanisms Of Tet Functionmentioning
confidence: 99%
“…In addition, both TET1 and TET2 deposit 5hmC in mRNAs in genes that are fundamental for pluripotency, such as Jarid2 and Eed , and can result in reduced mRNA stability (Lan et al, 2020 ). As a consequence of the transcript destabilization, pluripotency genes that would be expressed too highly acquire appropriate expression levels and adequately repress the expression of lineage-specifying factors (Lan et al, 2020 ). As the ES cells receive differentiation cues, the pluripotency factors are rapidly turned off and the lineage-specifying factors are upregulated to drive the differentiation process with efficiency (Lan et al, 2020 ).…”
Section: Mechanisms Of Tet Functionmentioning
confidence: 99%
“…Besides its binding to DNA, more recently TET2 has also been shown to interact with RNA in vitro and in vivo (Fu et al, 2014 ; Guallar et al, 2018 ; Shen et al, 2018 ; He et al, 2020 ; Lan et al, 2020 ). Indeed, and in line with the observation that TET2 is less strongly associated to chromatin than TET1 (Vella et al, 2013 ), its recruitment to chromatin was recently shown to be facilitated by RNA and decreased upon global transcriptional inhibition (Guallar et al, 2018 ).…”
Section: Tet2 Protein Structure and Functionmentioning
confidence: 99%
“…Although TET2 DNA-binding domain (DBD) and RBR domain have been mapped to different regions of the protein ( Figure 1A ) both were found to fold in proximity in human TET2 (Hu et al, 2013 ). Thus, it will be important to address how TET2 affinity and preference for RNA or DNA is regulated in the context of chromatin, where both nascent RNAs and genomic DNA can be oxidized (Chen et al, 2013 ; Hon et al, 2014 ; Guallar et al, 2018 ; Lan et al, 2020 ). Importantly, overexpression of full-length TET2 in HEK293T cells showed no catalytic activity in m 5 C in RNA, in contrast to TET2 catalytic domain, suggesting negative regulatory functions of the N-terminal domain on TET2 function on RNA oxidation (Fu et al, 2014 ).…”
Section: Tet2 Protein Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation